The emotional responses of university students: before and during the enforcement of the Covid-19 movement control order (MCO) / Wan Hartini Wan Zainodin ... [et al.] - Wan Zainodin, Wan Hartini; Ibnu, Ireena Nasiha; Muhammad Dimyati, Nurul Iman; Hussein, Eliza Ezzauddin; Md Redzuan, Ahmad; Muhamad Ali, Muhammad Naim (Centre For Media And Information Warfare Studies, 2021)
The aim of this study was to identify university students’ reactions during the enforcement of Movement Control Order (MCO) during COVID-19. As many of 486 students were involved as respondents throughout Malaysia to answer the survey for this study. The survey instrument was prepared in Likert Scale of 5 form to evaluate their responses. Descriptive statistics were interpreted in form of mean and standard deviation using Statistical Package for Social Sciences (SPSS) software. The data showed that students, both male and female recorded a relieved response towards the government’s efforts and action to fight the virus, as much as they also fear of being infected with the virus. Nevertheless, they also reported a confusion towards instruction issued by government or authorities which were inconsistent. Along the study, researchers also found the student, both male and female are less worried when they are with the families but highly concerned about the internet facilities to attend to lectures at universities via online platforms. At the same time, financial concerns arose in the study with a significant number during this challenging period of battling with the pandemic.